Burying Mohamed Ali Jauhar: The Life and Death of the Meccan Republic - John M. Willis (Arabian Humanities)
This article looks at the hitherto ignored project by the Indian Khilafat Movement to establish a republican government in the city of Mecca after the collapse of the Ottoman Empire. It argues that while activists of the Khilafat Movement were able to articulate an ethical vision of a transnational state rooted in the Islamic concept of fraternity (ikhvat), they were unable to effectively bring this vision to bear on the domain of the political, especially in the confrontation with the emerging power of the Saudi state and its intellectual allies.